How to Become a Patent Translator: Tricks and Tips – Notions of Text Genre and Ceremony to the Rescue - Aragonés Lumeras, Maite (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2010)
Before starting to translate patents and patent abstracts, translators – who are not discipline experts – need to be aware of the context of text genre production and the communicative purposes and intentions to make sure they are conveying the intended meaning in the accepted manner (of the typical ceremony) in order not to shock the recipient and distort the author’s original intent. This article aims to present the results of a study that analyzes both the moves of original patent abstracts in four languages (Chinese, Spanish, French and English) and four disciplines (medicine, chemistry, telecommunications, and IT) and the rhetorical value of linguistic choices (i.e., modality, verb tense, passive voice, adverbs and adjectives). The methodology used is twofold: qualitative so as to explain the text production context according to certain parameters related to text genre and give a better interpretation to the quantitative results, and quantitative so as to conduct a linguistic analysis of the patent abstracts. Text samples were chosen according to date of publication, original language and discipline, and form a corpus of 200 texts. The results appear to show that discipline does not play a major role in the linguistic choices made by the abstractors, and that boosting and hedging are both rhetorical ways to combine private intentions and collective purposes, while satisfying institutional requirements and recipients’ expectations.